2016
DOI: 10.1371/journal.pcbi.1004892
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Co-expression Analysis Reveals Distinct Functional Modules, Co-regulation Mechanisms and Clinical Outcomes

Abstract: Co-expression analysis has been employed to predict gene function, identify functional modules, and determine tumor subtypes. Previous co-expression analysis was mainly conducted at bulk tissue level. It is unclear whether co-expression analysis at the single-cell level will provide novel insights into transcriptional regulation. Here we developed a computational approach to compare glioblastoma expression profiles at the single-cell level with those obtained from bulk tumors. We found that the co-expressed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 52 publications
(54 reference statements)
1
30
0
2
Order By: Relevance
“…However TSPAN8 promote cancer cell stemness via activation of Hedgehog signaling 37 Systems biology approaches can provide immediate functional insights by revealing interactions between genes 39 . A motivation for WGCNA is that genes functioning together are regulated or co-expressed together 40 . Ballouz and cauthor 41 suggested a minimal of 20 samples to predict meaningful functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However TSPAN8 promote cancer cell stemness via activation of Hedgehog signaling 37 Systems biology approaches can provide immediate functional insights by revealing interactions between genes 39 . A motivation for WGCNA is that genes functioning together are regulated or co-expressed together 40 . Ballouz and cauthor 41 suggested a minimal of 20 samples to predict meaningful functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Two genes, NOSTRIN and ADGRG6, were shared by 66% of LTS, and have been reported before to be associated with PDAC survival. 40,53 Drugs bind to their target proteins and perturb the transcriptome of a cancer cell 54 . In our study, analytic functional analysis of individual PEEPs helped to decode homogeneity patterns within LTS.…”
Section: Discussionmentioning
confidence: 99%
“…For H. sapiens, Wang and colleagues recently compared the expression profiles of bulk tissue of glioblastoma patients to expression profiles at single-cell level [35]. Interestingly, they found that coexpression in bulk samples was stronger associated with similar gene function than that in single cell samples.…”
Section: B)mentioning
confidence: 99%
“…Also genes in eukaryotic genomes have been reported to have a tendency to cluster when showing similar expression, and the genes in these clusters tend to have related functions [28][29][30][31][32][33]. Wang and colleagues, as well as Barkai and colleagues showed that if two eukaryotic genes have the same expression levels in different conditions, they are likely to be members of the same protein complex or to participate in the same biological pathways [34,35]. Also, Lee and Sonnhammer reported that genes involved in the same biochemical pathways tend to gather in various eukaryotic genomes [31].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, clustering analysis was used to identify and characterize cell types in various tissues and tumors in the colon 19 , brain 20 , blood 12 , and lung 21 , with the overall aim of finding key stem and progenitor cell populations involved in tissue development, repair, and tumorigenesis. Another application is to find sets of coordinately regulated genes in order to find gene modules 11,22,23 . Such clusters of genes (or other features such as single-nucleotide polymorphism (SNPs) 24 ) can be further analyzed by gene set enrichment approaches to identify gene annotations 25 (e.g.…”
mentioning
confidence: 99%